Pengaruh Beberapa Jenis Pupuk dan Umur Bibit terhadap Pertumbuhan dan Hasil Tanaman Padi (Oryza sativa L.) - I KADEK WAHYU WIDIATMIKA; GEDE WIJANA; I NENGAH ARTHA (Agrotrop : Journal on Agriculture Science, 2017)
The Influence of Several Types of Fertilizers and Seeds Against Growth and Rice Yields (Oryza sativa L.). The research was carried out in a plastic house located in Banjar Kumuda Loka, Telaga Village, Busungbiu District, Buleleng Regency. The study was conducted from January 2017 to April 2017. The purpose of this study was to determine the type or combination of fertilizers and the age of the best seeds used that can provide maximum growth and yield of rice crops. This study was prepared using Factorial Randomized Block Design (RBD) with two factors. The first factor is the provision of fertilizer consisting of four level namely; fertilizing the farmer's way, organic fertilizer (solid + liquid), chemical fertilizer and organic fertilizer + chemical. The 2nd factor is the age difference of seeds consisting of three level namely; seed germinate, seven days after germinate and fourteen days after germinate. Each treatment was repeated three times. The results showed that the interaction between fertilization and seeding age had a significant effect on panicle length and the real impact on the harvest index. In single fertilizer were very significant to plant height, number of leaves, number of maximum and productive tillers, leaf area, number of panicles per hill, dry yield of harvest and dry oven per hill, Heavy wet and dry straw oven. While the treatment of seedlings had significant effect on plant height, number of leaves, number of maximum tillers, number of grains per panicle, panicle length and weight of grain per panicle. The highest yield (6.58 tons/ha) was obtained from a combination of organic and chemical fertilization with seeding age of 7 days after germinate.